2022
DOI: 10.3389/fgene.2021.772415
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of the Complete Chloroplast Genomes of Nine Paphiopedilum Species

Abstract: Paphiopedilum is known as “lady’s or Venus” slipper orchids due to its prominent shoe-shaped labellum, with high ornamental value. Phylogenetic relationships among some species in Paphiopedilum genus cannot be effectively determined by morphological features alone or through the analysis of nuclear or chloroplast DNA fragments. In order to provide aid in understanding the evolutionary and phylogenetic relationship in Paphiopedilum at chloroplast (cp) genome-scale level, the complete cp genomes of six Paphioped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 77 publications
(109 reference statements)
1
4
0
Order By: Relevance
“…The SSRs numbers in the LSC region of plastome of R. coccinea and R. philippinensis are 53 and 47, respectively. The distribution of SSR in the four species of Renanthera was consistent with that of most angiosperms (Xu et al, 2021;Sun et al, 2022;Xia et al, 2022).…”
Section: Discussionsupporting
confidence: 68%
“…The SSRs numbers in the LSC region of plastome of R. coccinea and R. philippinensis are 53 and 47, respectively. The distribution of SSR in the four species of Renanthera was consistent with that of most angiosperms (Xu et al, 2021;Sun et al, 2022;Xia et al, 2022).…”
Section: Discussionsupporting
confidence: 68%
“…The comparative analysis of variation information in different regions indicated that the IR regions were highly conserved compared to the LSC and SSC regions, as reflected by the fact that <6.5% of the SNPs that had been identified in this study were located within the IR regions even though IR regions constituted about one-third of the chloroplast genomes ( Figures 1A , 2A ; Supplementary Table 3 ). The low level of variant sites and nucleotide diversity observed in the IR regions was very common among plant chloroplast genomes (Choi et al, 2016 ; Wang et al, 2019 , 2022 ; Sun et al, 2022 ). In addition, the intergenic regions had greater divergence than the exon and intron regions ( Figure 2C ; Supplementary Table 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it could also be that RPs that fail to assemble into ribosomes are rapidly ubiquitinated and degraded in the nucleus in a proteasome-dependent manner as previously described. 88 Nevertheless, since the populations of ribosome subunits after 60 min of stimulation have different protein composition to those seen during quiescence, it appears that another process is responsible for the diversity of ribosomes raising the possibility that RPs could be exchanged using de novo synthesized RPs produced during quiescence exit. On the other hand, 80S ribosomes from quiescent cells could be recycled to polysomes once translational activity is induced.…”
Section: Discussionmentioning
confidence: 99%